Modelling Emergency Scenarios using Algebraic High Level Net Transformation Systems with Net Patterns - Trollmann, Frank; Kern, Maximilian; Albayrak, Sahin (Electronic Communications of the EASST, 2011)
Emergency operations are a good case study for dynamic systems. Their size and high dynamicity make modelling them a challenging task. Algebraic high level net transformation systems are a well suited technique for modelling such dynamic systems. They consist of an algebraic high level net and a set of graph transformation rules. The net reflects the initial state of the operation and the transformation rules can be used to adapt this state to reflect the dynamicity of the operation. The applicability of graph transformation rules depends on the existence of a match morphism. While designing the algebraic high level net transformation system the designer has to ensure the existence of the right match morphisms for all reachable runtime states. This can be a tedious and error prone task for the designer. This paper uses a case study for modelling emergency operations with algebraic high level net transformation systems to show how the notion of net patterns can help the designer to cope with rule applicability.